Synthesis and Characterization of 1,2-disubstituted -3-(pyrimidine-2-yl)-2,3-dihydro-1H-1,3-diazepine-4,7-dione - Ahmad, Shayma M (Al-Nahrain Journal of Science, 2018)
1,2-disubstituted-3-(pyrimidine-2-yl)-2,3-dihydro-1H-1,3-diazepine-4,7-dione were prepared from 2-amino pyrimidine via few steps were found to be useful synthesis for fully unsaturated monocyclic seven-membered heterocyclic ring.In this work the Schiff bases (1-3) was prepared from condensation 2-amino pyimidine with ketones and aldehydes, and then converted into 1,3-oxazepine derivatives(4-6) from maleic anhydride in dry dioxane. Treatment of (4-6) with different amines compounds (hydrazine, 4- amino antipyrine, thiosemicarbazide, and 2-aminothiazole) gave the corresponding 1,3-diazepine derivatives )7-18)..Characterization of 1, 3-diazepine derivatives determined by physical properties and chemical structure confirmed by1 HNMR and FTIR techniques. -